Peat soil treatment using hydrogen peroxide and its adsorption towards potassium ion (K+) in aqueous solution - Galuh Yuliani; Suci Karina; Mita Nurhayati; Siska Mutiara; Mamun Mollah; Shangeetha Ganesan (Universitas Sebelas Maret, 2025)
Peat soil contains functional groups such as carboxylic acid and hydroxyls that bind metal ions and organic compounds in solution. However, the adsorption capacity of natural peat soil is still considered low. Therefore, this study aims to alter the peat surface using a hydrogen peroxide solution and to utilize the resulting peat as an adsorbent for K+ ions in an aqueous solution. Peat soil was treated with a 10% hydrogen peroxide solution for 30 minutes. The infrared spectra of the treated peat indicated an increase in the intensity of hydroxyl groups (-OH) at 3400 cm-1 and a sharp increase in carboxylic groups (-COOH) at 1700 cm-1. SEM photos showed that the porosity of the treated peat was higher, probably due to oxidation reactions that resulted in new pores on the surface, and BET analysis confirmed the increase in surface area upon treatment. During the adsorption experiment, the residual concentrations of K+ ions were determined using AAS. The adsorption capacities of raw and treated peat were 37.40 mg g-1 and 59.53 mg g-1, respectively. When fitted using Langmuir and Freundlich adsorption isotherm models, the adsorption data plots followed the Freundlich isotherm model, indicating reversible adsorption on heterogeneous surfaces. The Density Functional Theory (DFT) calculation showed that the interaction energy between peat soil and K+ ions was lower after treatment, indicating that K+ ions bind to exchange sites on the treated peat soil.